2018
DOI: 10.1007/s13365-018-0679-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age, HIV, and HIV-associated clinical factors on neuropsychological functioning and brain regional volume in HIV+ patients on effective treatment

Abstract: It is yet unclear if people infected with human immunodeficiency virus (HIV+) on stable, combined antiretroviral therapies (cARTs) decline with age at the same or greater rate than healthy people. In this study, we examined independent and interactive effects of HIV, age, and HIV-related clinical parameters on neuropsychological functioning and brain regional volume in a sizable group of Polish HIV+ men receiving cART. We also estimated the impact of nadir CD4 cell count, CD4 cell count during participation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 47 publications
(92 reference statements)
0
12
0
1
Order By: Relevance
“…Regression analysis also showed that older age was associated with poorer performance in both tests. However, no interaction effect was observed Gawron et al (2018) [ 35 ] Cross-sectional Age as continuous variable and HIV serostatus Standard 6 Test (raw score) No premature age effect Both HIV and age independently contributed to the lower performance in NP test results although their interaction effect was not observed Cysique et al (2011) [ 39 ] Cross-sectional Age as continuous variable and HIV serostatus Standard 6 Global impairment score and Frascati No premature age effect Both age and HIV status were independently associated in the expected direction to the global impairment score. However, their interaction effect was not clear.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regression analysis also showed that older age was associated with poorer performance in both tests. However, no interaction effect was observed Gawron et al (2018) [ 35 ] Cross-sectional Age as continuous variable and HIV serostatus Standard 6 Test (raw score) No premature age effect Both HIV and age independently contributed to the lower performance in NP test results although their interaction effect was not observed Cysique et al (2011) [ 39 ] Cross-sectional Age as continuous variable and HIV serostatus Standard 6 Global impairment score and Frascati No premature age effect Both age and HIV status were independently associated in the expected direction to the global impairment score. However, their interaction effect was not clear.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies were conducted in the US while two studies originated from the UK [ 29 , 30 ], Italy [ 31 , 32 ], China [ 33 , 34 ], and Poland [ 35 , 36 ], and one was carried out in Japan [ 37 ], Brazil [ 38 ], and Australia [ 39 ]. No study was conducted in low-income countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that recruited unrepresentatively healthy HIV participants within their country (i.e. highly educated, stable on cART, with undetectable viral load and no neuropsychological confounds) did not observe premature cognitive ageing [33,34]. A Polish study [33] did not observe the premature cognitive ageing effect amongst 91 HIV‐positive and 95 HIV‐negative participants (age range: 23–75 years) who were recruited from an infectious disease hospital and received standard neuropsychological testing.…”
Section: Discussionmentioning
confidence: 99%
“…highly educated, stable on cART, with undetectable viral load and no neuropsychological confounds) did not observe premature cognitive ageing [33,34]. A Polish study [33] did not observe the premature cognitive ageing effect amongst 91 HIV‐positive and 95 HIV‐negative participants (age range: 23–75 years) who were recruited from an infectious disease hospital and received standard neuropsychological testing. All the participants in this study were males who were highly educated (≥12 years of education), and clinically stable (no active OI, active syphilis, current hepatitis C coinfection, alcohol or substance abuse, major psychiatric illnesses, liver or renal insufficiency, and had viral load < 60 copies/mL).…”
Section: Discussionmentioning
confidence: 99%